2014
DOI: 10.1186/s12917-014-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol with oxygen insufflation corrects etorphine-induced hypoxaemia in chemically immobilized white rhinoceros (Ceratotherium simum)

Abstract: BackgroundOpioid-induced immobilization is associated with severe respiratory depression in the white rhinoceros. We evaluated the efficacy of butorphanol and oxygen insufflation in alleviating opioid-induced respiratory depression in eight boma-managed rhinoceros.ResultsChemical immobilization with etorphine, azaperone and hyaluronidase, as per standard procedure for the white rhinoceros, caused severe respiratory depression with hypoxaemia (PaO2 = 27 ± 7 mmHg [mean ± SD]), hypercapnia (PaCO2 = 82 ± 6 mmHg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…; Haw et al. ). We therefore compared butorphanol with nalbuphine because results from studies in mice (Schmidt et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Haw et al. ). We therefore compared butorphanol with nalbuphine because results from studies in mice (Schmidt et al.…”
Section: Discussionmentioning
confidence: 99%
“…In wildlife immobilization, butorphanol is used to reverse etorphine-induced respiratory depression, especially in opioid-sensitive species, such as the white rhinoceros (Burroughs et al 2012). However, recent studies indicate that butorphanol is not an effective l-antagonist in rhinoceros as was previously thought (Miller et al 2013;Haw et al 2014). Evidence from human and rodent studies indicates that nalbuphine, which is not currently used in veterinary medicine, may be a better l-opioid antagonist than butorphanol (Pallasch & Gill 1985;Schmidt et al 1985;Zucker et al 1987).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We have thus demonstrated that CX1942 attenuates etorphine-induced respiratory depression in goats, and that it may be useful for improving the welfare of immobilized wild ungulates. Previous studies investigating the effects of etorphine on respiratory and cardiovascular systems have used goats as a model for wild ungulates because the use of a domesticated animal in a controlled setting limits the confounding effects of a capture-induced stress response, and allows for the better determination of a drug's pharmacodynamic effects (Heard et al 1990(Heard et al , 1996Buss & Meltzer 2001;Meyer et al 2015). However, the degree of sensitivity to opioid-induced respiratory depression varies amongst species (Burroughs et al 2012).…”
Section: Discussionmentioning
confidence: 99%